Remote Cooperative Group Strategy Enables Ligands for Accelerative Asymmetric Gold Catalysis - Wang, Zhixun; Nicolini, Corrado; Hervieu, Cedric; Wong, Yuk-Fai; Zanoni, Giuseppe; Zhang, Liming (Journal of the American Chemical Society, 2017)
An accelerative asymmetric gold catalysis is achieved for the first time via chiral ligand metal cooperation. An asymmetrically positioned remote amide group in the designed chiral binaphthyl-based ligand plays the essential role of a general base catalyst and selectively accelerates the cyclizations of 4-allen-1-ols into one prochiral allene face. The reactions are mostly highly enantioselective with achiral substrates, and due to the accelerated nature of the catalysis catalyst loadings as low as 100 ppm are allowed. With a pre-existing chiral center at any of the backbone sp3-carbons, the reaction remained highly efficient and most importantly maintained excellent allene facial selectivities regardless of the substrate stereochemistry. By using different combinations of ligand and substrate enantiomers, it is now possible to access all four stereoisomers of versatile 2-vinyltetrahydrofurans with exceedingly high selectivity. The underpinning design of this chemistry reveals a novel and conceptually distinctive strategy to tackle challenging asymmetric gold catalysis, which to date has relied on decelerative asymmetric steric hindrance approaches.